ANALYSIS OF THE INFLUENCE OF WORK-LIFE BALANCE AND JOB STRESS THROUGH JOB SATISFACTION ON PERFORMANCE - Kaseng, Saharuddin; Adda, Harnida Wahyuni; Fadly, Moh. (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2024)
The purpose of this study was to examine and analyze the influence of work-life balance and job stress on the performance of nurses at RSUD Mokopido Tolitoli, both directly and indirectly through job satisfaction. The study population consisted of all ASN nurses working across various units at RSUD Mokopido Tolitoli. Using Slovin's formula, a sample size of 64 respondents was determined. The sampling technique employed was proportional stratified random sampling. Questionnaires were distributed directly to ASN nurses at RSUD Mokopido Tolitoli to collect data, which was subsequently analyzed using the Structural Equation Modeling - Partial Least Squares (SEM-PLS) technique with the SmartPLS 4.0 statistical tool. The results of the research findings confirmed that work-life balance can directly affect significantly and positively the job satisfaction of nurses at Mokopido Tolitoli Hospital, work-life balance can directly affect significantly and positively the performance of nurses at Mokopido Tolitoli Hospital, work stress can directly affect significantly and positively the job satisfaction of nurses at Mokopido Tolitoli Hospital, work stress cannot directly affect the performance of nurses at Mokopido Tolitoli Hospital, job satisfaction can directly affect significantly and positively the performance of nurses at Mokopido Tolitoli Hospital. In addition, work-life balance through job satisfaction can directly and significantly affect positively the performance of nurses at Mokopido Tolitoli Hospital, and job stress through job satisfaction can directly and significantly affect positively the performance of nurses at Mokopido Tolitoli Hospital